INFLUENCING FACTORS OF SPORT VOLUNTEERING AMONG EU CITIZENS - Nagy, Tamás; Paár, Dávid; Laczkó, Tamás (Stadium - Hungarian Journal of Sport Sciences, 2022)
If there were a ‘country of volunteers,’ it would be one of the most populous countries in the world, with almost 1 billion people involved in some form of volunteering worldwide. Volunteers play an essential role in the smooth running and operation of sports associations and the performance of the assigned tasks. Our research examines the extent to which they contribute to volunteering along with different socio-demographic variables. For our analysis, we used data from the European Commission in December 2017 in 28 European Member States (28,031 people). We used ten independent factors that may influence participation in volunteering. We examined by chi-square test whether there was a relationship with the performance of sports volunteering for the selected variables. Subsequently, incorporating all these variables into a logistic regression model, we estimated how much it contributes to volunteering. The significance level was p